Ocena potrzeb zdrowotnych nauczycieli szkół średnich w kontekście zagrożeń zdrowia związanych z miejscem pracy = Assessment of the health needs of secondary school teachers in the context of health risks at the workplace - Katarzyna Wodzyńska; Joanna Skonieczna; Dominik Olejniczak; Urszula Religioni (Kazimierz Wielki University, 2016)
Wodzyńska Katarzyna, Skonieczna Joanna, Olejniczak Dominik, Religioni Urszula. Ocena potrzeb zdrowotnych nauczycieli szkół średnich w kontekście zagrożeń zdrowia związanych z miejscem pracy = Assessment of the health needs of secondary school teachers in the context of health risks at the workplace. Journal of Education, Health and Sport. 2016;6(4):193-210. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.50115 http://ojs.ukw.edu.pl/index.php/johs/article/view/3463   The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 20.03.2016. Revised 17.04.2016. Accepted: 17.04.2016.     OCENA POTRZEB ZDROWOTNYCH NAUCZYCIELI SZKÓŁ ŚREDNICH W KONTEKŚCIE ZAGROŻEŃ ZDROWIA ZWIĄZANYCH Z MIEJSCEM PRACY Assessment of the health needs of secondary school teachers in the context of health risks at the workplace   Katarzyna Wodzyńska, Joanna Skonieczna1, Dominik Olejniczak1, Urszula Religioni2   1Zakład Zdrowia Publicznego, Warszawski Uniwersytet Medyczny, ul. Banacha 1a, 02-097 Warszawa 2Szkoła Główna Handlowa, Kolegium Ekonomiczno-Społeczne, ul. Wiśniowa 41, 02-520 Warszawa   mgr Katarzyna Wodzyńska mgr Joanna Skonieczna dr n. med. Dominik Olejniczak dr n. o zdr. Urszula Religioni   Słowa kluczowe: potrzeba zdrowotna, nauczyciele, promocja zdrowia, miejsce pracy Key words: need care, teachers, health promotion, workplace   Streszczenie Wstęp Nauczyciel w swoim zawodzie narażony jest na wiele niekorzystnych czynników. Miejsce pracy oraz warunki jakie w nim panują, w znacznym stopniu wpływają na zdrowie i samopoczucie. Odpowiednia ergonomia stanowiska pracy jest w tej kwestii bardzo istotna. Głównym celem pracy jest zbadanie i ocena potrzeb zdrowotnych nauczycieli, które są związane z charakterem, miejscem wykonywanej  pracy oraz występujących w niej zagrożeń zdrowia. Materiał i metody W przeprowadzonym badaniu ankietowym, dotyczącym wykonywania zawodu nauczyciela wzięło udział 283 nauczycieli z dwunastu  szkół średnich znajdujących się na terenie województwa mazowieckiego. Wypełniony przez nauczycieli kwestionariusz składał się z 21 pytań dotyczących zagadnień związanych z wykonywaniem zawodu. Uzyskane wyniki poddano analizie statystycznej z wykorzystaniem testu Chi2 Pearsona oraz R Spearmana. Za istotne różnice uznano te, dla których prawdopodobieństwo p<0.05. Wyniki Blisko połowa respondentów wskazała, że praca ma istotny wpływ na zdrowie. Według 20,5% badanych wykonywany zawód w średnim stopniu wpływa na stan zdrowia, zaś 18% wszystkich respondentów uważa, że udział czynników pracy w ogólnym samopoczuciu jest niewielki. Zmęczenie jest jedną z najczęstszych dolegliwości wśród nauczycieli. 18,1% badanych deklaruje że odczuwa je codziennie, zaś u 39,7% respondentów występuje ono często, bo 2-3 razy w tygodniu. Wnioski Uzyskane wyniki pozwalają wyciągnąć wniosek, iż nauczyciele mają świadomość wpływu pracy na zdrowie, jak również są świadomi dolegliwości jakie mogą występować w związku z pracą.   Abstract Background Teacher in his profession is exposed to many adverse factors. Place of work and the conditions that prevail in it, seriously affecting the health and well-being. Appropriate workplace ergonomics in this very important issue. The main aim of this paper is to examine and assess the health needs of teachers, which are related to the nature, place of work and associated health risks. Material and methods In a survey conducted concerning the teaching profession was attended by 283 teachers from twelve schools located in the Mazowieckie Province. Completed by the teacher questionnaire consisted of 21 questions on issues related to his profession. The results were statistically analyzed using Pearson Chi2 test and Spearman R. The significant difference was that for which the probability of p <0.05. Results Nearly half of the respondents indicated that the work has a significant impact on health. According to 20.5% of their profession in the medium affects the health, while 18% of all respondents believe that the participation of agents working in the general well-being is low Fatigue is one of the most common complaints among teachers. 18.1% of respondents declared that they felt it every day, and in 39.7% of the respondents, it is often because 2-3 times a week. Conclusion The results lead to the conclusion that teachers are aware of the impact of work on health, as well as being aware of the problems which may arise in connection with work.